Beneficial Effects of Human Anti-Interleukin-15 Antibody in Gluten-Sensitive Rhesus Macaques with Celiac Disease - Sestak, Karol; Dufour, Jason P.; Liu, David X.; Rout, Namita; Alvarez, Xavier; Blanchard, James; Faldas, Anne; Laine, David J.; Clarke, Adam W.; Doyle, Anthony G. (Frontiers in Immunology, 2018)
Over-expression of interleukin-15 (IL-15) is linked with immunopathology of several autoimmune disorders including celiac disease. Here we utilized an anti-human IL-15 antibody 04H04 (anti-IL-15) to reverse immunopathogenesis of celiac disease. Anti-IL-15 was administered to 6 gluten-sensitive rhesus macaques with celiac disease characteristics including gluten-sensitive enteropathy, and the following celiac-related metrics were evaluated: morphology (villous height / crypt depth ratio) of small intestine, counts of intestinal intraepithelial lymphocytes, IFN-γ-producing CD8+ and CD4+ T cells, plasma levels of anti-gliadin and anti-intestinal tissue transglutaminase (TG2) IgG antibodies, as well as peripheral effector memory (CD3+CD28-CD95+) T cells. Anti-IL-15 treatment reversed the clinically relevant disease endpoints, intraepithelial lymphocyte counts and villous height / crypt depth ratios within jejunal biopsies to normal levels (P<0.001). Additionally, intestinal CD8+ and CD4+ T cell IFN-γ production was reduced (P<0.05). Extra-intestinally, anti-IL-15 treatment reduced peripheral NK cell counts (P<0.001) but otherwise non-NK peripheral lymphocytes including effector memory T cells and serum blood chemistry were unaffected. Overall, providing the beneficial disease-modulatory and immunomodulatory effects observed, anti-IL-15 treatment might be considered as a novel therapy to normalize intestinal lymphocyte function in celiac disease patients with gluten-sensitive enteropathy.